Faktor-faktor Pendorong Keniatan Pekerja Lansia untuk Melanjutkan Bekerja - Waskito, Jati (Benefit, 2014)
This study aims to conceptualize the notion of âolder workerâ intention to continue paid working and to validate a scale of measuring the impact of work related factors on older workerâ intentions to continue in employment. This study uses a cross-sectional, survey-based, self report strategy to gather data. The findings the importance of working, the individuals interest outside works, management and organizational factors, work flexibility, and work attachment are the important things that can influenceÂ  the older worker to continue paid working